Model Pembelajaran Generatif Dalam Upaya Meningkatkan Hasil Belajar Matematika - Madio, Sukanto Sukandar (Department of Mathematics Education Program IPI Garut, 2012)
The aim of this research is to analyze, (a) mathematical achievement capability of student after learning by Generative model, (b) mastery learning of student after learning by Generative model, and (c) student activities while learning Generative models. This research is directed to class action research in one of public high school in Garut as population subject are all eleventh-grade student by taking one class of 41 students as a sample. The result of research shows, (a) mathematical achievement capability of student after learning by Generative model have been changed (increased) in score that received by student, of cycle I to cycle II, of cycle II to cycle III, and of cycle III to cycle IV, (b) mastery learning of student after learning by Generative models not reached yet on cycle I, but reached on cycle II, cycle III, and cycle IV, (c) Learning Condition of implementation of Generative Model have been increased to be better and student learning activity have been increased to be better too.